Repensar els estudis de Biblioteconomia i Documentació a Espanya: traspassant els límits/Rethinking studies LIS Spain: across boundaries - Ortiz-Repiso, Virginia (BiD (Barcelona, Spain), 2015)
The main objectives of this paper are to provide an overview of the current state of studies in library and information science in Spanish universities and to discuss the challenges this discipline is facing and the strategies that might strengthen the position of LIS-related studies and professional practice. But the paper also reconsiders why LIS in Spain is crossing the boundaries in two ways. First, it examines interdisciplinarity in LIS and identifies some of the travel companions LIS has made on its journey across the boundaries; and second, it analyzes the negative social repercussions LIS has experienced. Finally, the paper proposes initiatives to mitigate the low visibility of LIS education and the profession as a whole.